The analysis of phrasal verbs found in blood diamond movie by edward zwick - Yasin, Muhammad Reza Jufri; Nugraha, I Gusti Bagus Wahyu; Jayantini, I Gusti Agung Sri Rwa (Institut Pariwisata dan Bisnis Internasional, 2021)
This study investigated the types of phrasal verbs encountered in a movie entitled Blood Diamond. The problems of this study is what types of phrasal verb are found in the movie entitled Blood Diamond?. This study employed descriptive and qualitative method to provide a well-organized description regarding the problems being identified. The data of this study were obtained by observation method through four stages. Firstly, watching the Blood Diamond movie. Secondly, finding and taking notes the phrasal verb spoken by the characters in the movie Blood Diamond. Reading the online movie script and finally the writer categorized the types of data based on the theory proposed by McCarthy & O’Dell (2007:8). There were two types of phrasal verb encountered namely transitive and intransitive phrasal verb, in which transitive phrasal verb can be specialized into separable or non-separable transitive phrasal verb. The result of the study demonstrated that there are 8 data of phrasal verbs discovered in the movie Blood Diamond consisting 4 transitive phrasal verbs and 4 intransitive phrasal verbs.